EVOLUTION OF PROPERTIES OF IRRIGATED GRASSLAND SOILS - Shakhobiddin Turdimetov; Zarkum Rakhimov (International Scientific and Current Research Conferences, 2021)
This article discusses the change in the mechanical, physical and chemical properties of irrigated grassland soils of the Mirzachul oasis during irrigation. The regularities of evolutionary processes in soil were analyzed.